2006
DOI: 10.1055/s-2006-925023
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Clip Application for Postoperative Residual Esophageal Duplication Cyst

Abstract: A 35−year−old woman presented with coughing, left−sided chest pain, and high−grade intermittent fever that had persisted for 3 weeks. She had received a course of antibiotics for a week, with− out any response. At admission, the clinical examination was un− remarkable except for toxemia. The chest examination did not reveal any abnormality. A chest radiograph showed mediastinal widening and chest computed tomography revealed a cyst 8 10 4 cm in size communicating with the mid−esophagus, with an air±fluid level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…One postoperative complication was reported in a 35‐year‐old woman, who developed chest pain and fever on her POD 10. A swallow study revealed a leakage into the posterior mediastinum, which was successfully resolved by endoscopy applying metallic clips [35]. One 30‐year‐old male patient died in whom a thoracotomy was performed for resecting an EDC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One postoperative complication was reported in a 35‐year‐old woman, who developed chest pain and fever on her POD 10. A swallow study revealed a leakage into the posterior mediastinum, which was successfully resolved by endoscopy applying metallic clips [35]. One 30‐year‐old male patient died in whom a thoracotomy was performed for resecting an EDC.…”
Section: Discussionmentioning
confidence: 99%
“…If the cyst is not promptly diagnosed, it might cause severe complications such as perforation [20,[27][28][29][30], mild bleeding [31,32] intramural hematoma [33] and massive hemorrhage into the pleura space [34]. Infection is another known complication of EDC [35][36][37][38]. Agarwal et al [39] and Tomar et al [40] reported two young adults who presented with an EDC masquerading pericarditis and post-infective bronchiectasis, respectively.…”
Section: Discussionmentioning
confidence: 99%